Development of Biodiversity Encyclopedia Based on Flipbook to Improve Student Learning Outcomes in Senior High School 6 Samarinda - Sutiwi; Elsje Theodora Maasawet; Muh Amir Masruhim; Usman Usman; Herliani Herliani; Ahmad Ahmad (Postgraduate, University of Mataram, 2025)
This study aims to develop a flipbook-based encyclopedia on the biodiversity of the Plantae kingdom for Grade X students at SMAN 6 Samarinda to enhance their learning outcomes. The research employed the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. A total of 30 students participated in the implementation stage. The effectiveness of the product was evaluated using a one-group pretest-posttest design. Data were collected through interviews, needs analysis questionnaires, expert validation sheets, teacher assessments, student response questionnaires, and pretest-posttest multiple-choice questions. The feasibility results from experts comprising material, media, and language specialists showed high validity, with scores of 91.75, 78.88, and 90% respectively, indicating the product is